Ophthalmological and radiological findings in patients of hypertensive crisis reporting to an intensive care setting - Salomi Samuel Bhandare; Sneha Roy; Utsav Anand Mani; Kartika Gautam (Heart India, 2023)
Background: The term “hypertensive crisis (HC)” is used to describe both hypertensive emergencies and hypertensive urgencies. Hypertensive emergencies are characterized by the presence of target organ damage, whereas hypertensive urgencies do not involve such organ damage. Methods: The main objective of this research was to evaluate all prevalence and clinical profiles of HC in an intensive care unit (ICU). A consecutive type of nonprobability sampling was followed during the study period for the selection of the study sample. A total of 50 patients fulfilling the criteria of eligibility were used for this research with proper informed consent. Results: Of the 50 patients reporting to the ICU with hypertensive emergencies and urgency, the most common systemic involvement was neurological, followed by cardiac. On Electrocardiographic (ECG), ST-T wave changes were seen in 46% of cases, whereas left ventricular hypertrophy was reported in 22% of cases. Conclusions: Hypertensive retinopathy was the most common ophthalmological finding, SR-T wave changes were the most common ECG finding, and intracerebral hemorrhage was the most common computed tomography finding in patients of HC.